VALIDITY AND RELIABILITY OF BASIC MANIPULATIVE MOVEMENT SKILLS TESTS FOR EARLY CHILDREN 6-8 YEARS - Ashidiqie, Dawam; Siregar , Nofi Marlina; Sujarwo (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Basic motor skills assessment tests are widely used, including tests of manipulative basic movement skills. The basic manipulative movement skill test is used to measure the basic manipulative movement skills of early childhood. The purpose of this study was to find out whether it is suitable and effective for measuring basic manipulative movement skills in early childhood 6-8 years. The sample population used in this study were 30 different early childhood children aged 6-8 years in Pecallan Village, Natar District, South Lampung. Construct validity and reliability were calculated using Pearson's correlation with the results obtained that the study included 4 indicators, namely throwing, catching, hitting, and kicking, the results obtained were r count > r table (28; 5%) = 0.361. So it can be stated that all the indicator items used are valid. And based on the reliability test with Cronbach alpha, a value of 0.806 > 0.7 is obtained, so that it represents that these items are reliable for measuring the sample. In conclusion, thus that the manipulative basic movement skills test can be used to measure basic movement skills in early childhood 6-8 years.